Educandy assisted as learning media to improve critical thinking skills on light material in elementary school - Aditya Rizqi Putra Purnomo; Zulherman Zulherman (Inovasi Kurikulum, 2025)
The low critical thinking skills of students in science education serve as the primary background for this study. Therefore, this research and development aims to produce and test the effectiveness of an Edu-Game-based learning medium on the Educandy platform for the topic of Light in 5th-grade elementary school. This study employed the RnD method using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research involved media and material experts for feasibility testing, as well as 5th-grade students from three different elementary schools. The validation results from the experts indicated a feasibility rating of "Very Feasible". The effectiveness test, using the non-parametric Mann-Whitney U test, demonstrated effective results at SDN Batu Ampar 08 and SDN Dukuh 01. In contrast, the results at SDN Kebon Pala 11 were not effective. Thus, it is concluded that this learning medium is feasible for enhancing students' critical thinking skills, although one school showed a non-significant difference in N-Gain scores.   Abstrak Rendahnya kemampuan berpikir kritis peserta didik pada pembelajaran IPA menjadi latar belakang utama penelitian ini. Oleh karena itu, penelitian dan pengembangan ini bertujuan untuk menghasilkan dan menguji efektivitas media pembelajaran interaktif berupa Edu-Game pada platform Educandy untuk materi Cahaya di kelas V SD. Penelitian ini menggunakan metode RnD (Research and Development) dengan model pengembangan ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Penelitian ini melibatkan ahli dalam media dan materi sebagai penguji kelayakan, serta peserta didik kelas 5 SD dari 3 Sekolah Dasar yang berbeda. Berdasarkan hasil uji validasi oleh ahli, menunjukan kategori kelayakan “Sangat layak”. Hasil uji efektivitas dengan uji non-parametrik Mann Whitney U pada SDN Batu Ampar 08 dan SDN Dukuh 01 menunjukkan hasil efektif sedangkan SDN Kebon Pala 11 menunjukkan hasil tidak efektif. Dengan demikian dalam pengembangan media pembelajaran ini dalam meningkatkan critical thinking skill peserta didik dinyatakan layak meskipun terdapat satu sekolah yang menunjukkan hasil beda (N-Gain) yang tidak signifikan. Kata Kunci: Educandy; kemampuan berpikir kritis; pengembangan media pembelajaran; sekolah dasar